2018
DOI: 10.3390/cosmetics5030051
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid-layered Double Hydroxide Hybrid: A New Raw Material for Cosmetic Applications

Abstract: Bioactive ingredients from natural sources possess well-known positive effects in cosmetic applications. Among them, phenolic acids have emerged with very interesting potential. Caffeic acid (CAF) is one of the most promising active compounds because it possess antioxidant, anti-inflammatory, antitumoral and anti-wrinkle effects. In order to increase its local bioavailability in topical applications, the vehiculation of caffeic acid can lead to a new raw material of cosmetic interest. For this purpose, clay mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Based on the experiment, rutin has DPPH and H2O2 scavenging capacities better than caffeic acid. This finding is consistent Bastianini et al (2018) and Rusmana et al (2017), which successfully detected the antioxidant potential of rutin. Cervantes-Laurean et al (2006) suggest that flavonoids with vicinyl dihydroxyl groups in the B-ring inhibit iron and copper-catalyzed radical species growth.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Based on the experiment, rutin has DPPH and H2O2 scavenging capacities better than caffeic acid. This finding is consistent Bastianini et al (2018) and Rusmana et al (2017), which successfully detected the antioxidant potential of rutin. Cervantes-Laurean et al (2006) suggest that flavonoids with vicinyl dihydroxyl groups in the B-ring inhibit iron and copper-catalyzed radical species growth.…”
Section: Resultssupporting
confidence: 87%
“…Rutin has been reported to inhibit aging-related mitochondrial dysfunction in aged test rats by increasing oxygen consumption rate, GSH content, and SOD activity, signifying its antioxidant and antiaging potential (Li et al, 2016). Caffeic acid is the most promising antioxidant, antiinflammatory, and anti-wrinkle agent (Bastianini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis demonstrates the thermal stability of the SBA15‐type materials. The DSC spectrum indicates an endothermic process …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown to have anti-wrinkle activity in vivo [23]. Bastianini et al (2018) reported on the successful preparation of an innovative raw material for cosmetic applications. They described successful vehiculation of caffeic acid into anionic clay, which is a very promising hybrid for the cosmetic market because of its higher bioavailability and prolonged antioxidant activity [24].…”
Section: Caffeic Acid Bioactivitymentioning
confidence: 99%
“…Bastianini et al (2018) reported on the successful preparation of an innovative raw material for cosmetic applications. They described successful vehiculation of caffeic acid into anionic clay, which is a very promising hybrid for the cosmetic market because of its higher bioavailability and prolonged antioxidant activity [24]. Chao et al (2009) studied the anti-inflammatory properties of caffeic acid and ellagic acid and in their study, they demonstrated a cardioprotective effect of the tested compounds against dyslipidemia, hypercoagulability, oxidative stress, and inflammation in diabetic mice.…”
Section: Caffeic Acid Bioactivitymentioning
confidence: 99%